The finishing and cleaning of long parts in screw rotors - V. A. Lebedev; L. M. R. Al-Obaidi; N. S. Koval (Advanced Engineering Research)
Introduction. To search for effective methods of finishing and stripping of long-length parts, it is advisable to create a rotary-screw process system of a pass-through type. Its main working element is a screw rotor, which is a combination of flat elements of various shapes and sizes, multidirectional with respect to the helical lines around the perimeter. The purpose of this study is to justify the intensity of the machining process in devices equipped with a screw rotor.Materials and Methods. Metal removal is accepted as the main parameter determining the intensity of the machining process in screw rotors. Within the framework of the presented study, processing was performed on an experimental rotary-screw installation. The processing medium consisted of molded abrasive pellets of the PT 10x10 brand. The research conditions were as follows: loading volume (without part) — 60 %; rotor speed — 50 rpm; processing time – 30, 60, 90 min; rotor axis tilt angles — 0о and 5о. The influence of treatment modes and conditions on the process intensity was considered on plate samples with dimensions of 80×10×1 mm made of aluminum alloy D16T. To determine metal removal, the samples were weighed on Ohaus AX223 analytical balance before and after processing.Results. The patterns of metal removal from samples at different processing times, the location of samples in the working area of a screw rotor with different angles of inclination, and its speed are presented.Discussion and Conclusions. The regularities established in the course of research indicate the efficiency of rotaryscrew process systems for solving problems on the finishing treatment of long-length parts. The main factors that control such processing in devices with a screw rotor and affect its intensity (and, as a consequence, the process performance) are the screw rotor speed, the shape of the perimeter, and the axis angle.